A Research for Development of Instructional Management System on Chinese for Primary Schools in Thailand - Sae-jia, Hathai (Journal of Sinology (วารสารจีนวิทยา), 2016)
The objective of this research is to study the instructional management on Chinese for primary school in Thailand. The research was conducted by studying the current situations and problems of instructional management on Chinese for primary school, i.e. management, curriculum, instructional media, instructors, learners, and collaboration with other departments. The sample group in this research consists of 141 education institutes throughout Thailand, all of which offer the course of Chinese for primary school. Thereby, the said institutes include schools under the Office of the Basic Education Commission, Chinese language schools, private schools, and schools under Bangkok Metropolitan Administration. The data were collected by means of questionnaire and interview; and then the data were analyzed in order to find out the guidelines that could develop the instructional management system on Chinese for primary school in Thailand in a more efficient manner.